PENGELOLAAN RUANG TERBUKA HIJAU (RTH) TAMAN ASRI KOTA MOLEK KABUPATEN INDRAGIRI HULU - Hafiza "; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Green Open Space is intended to maintain the harmony and balance of the urban environmental ecosystem and create a balance between the natural environment and the artificial environment in urban areas as well as improve the quality of a healthy, beautiful, clean and comfortable urban environment. The purpose of this study is to describe how to manage the Green Open Space (RTH) of Taman Asri City, Molek City, Indragiri Hulu Regency, and to find out what obstacles are encountered in managing the Green Open Space (RTH) of Taman Asri City, Molek City, Indragiri Hulu Regency. The theory used in this research is Henry Fayol's management theory which consists of planning, organizing, directing, and controlling indicators. The type of research used is descriptive qualitative research. Data collection techniques were carried out by interview, observation, and documentation. The researcher uses the Miles and Huberman Model data analysis technique which consists of data reduction, data presentation, and conclusion/verification. The results showed that in the planning stage, the construction of the Taman Asri green space was built using funds built using the APBD budget. For its own management, it also uses APBD funds. In the organizing stage, there is a division of tasks between the parties involved. One of the main agencies is the Department of Public Works and Spatial Planning of Indragiri Hulu Regency, in which there are functions of the Human Settlements Sector as well as the Hygiene and Gardening Sector. In the briefing stage there is a directive function carried out by providing a motivational program to every officer in the field and also to the people who visit the green open space at Taman Asri, Molek City. At the control stage, regular evaluations are carried out every month to ensure that the work program for managing the green open space at Taman Asri Kota Molek is running as it should. Keywords: Management, Green Open Space, Beautiful Parks, Urban  Environment